Application of Technological Innovation in the Agricultural Sector to Promote Food in Indonesia - JA, Sudarma (Inspiring Law Journal, 2024)
The main problems faced in agricultural development are low productivity on a micro scale, total production on a macro scale, and the welfare of agricultural business actors themselves. In the short term, agricultural development aims to increase growth, but in the long term, the aim of agricultural development aims to provide price stability for business actors. In general, the direction of agricultural policy is to provide certainty for business continuity, both in the short and long term. The study was carried out using secondary data which was analyzed qualitatively using the Desk Research Method. The literature materials used in writing this research are several references originating from the results of research, studies and reviews of several papers which are then summarized into a work of scientific writing. That the type of agricultural technology innovation developed or implemented by farmers depends on the agrosystem conditions of the local area. There is a relationship between the application or adoption of agricultural technology innovation and the level of resilience of farming households. Farmers who more intensively implement technological innovation based on innovative agricultural business systems have a better level of food security compared to farmers who do not implement technological innovation based on innovative agricultural business systems